Compromised Conscience: A Scoping Review of Moral Injury Among Firefighters, Paramedics, and Police Officers - Lentz, Liana M.; Smith-MacDonald, Lorraine; Malloy, David; Carleton, R. Nicholas; Brémault-Phillips, Suzette (Frontiers in Psychology, 2021)
Background Public Safety Personnel (e.g., firefighters, paramedics, and police officers) are routinely exposed to human suffering and need to make quick, morally challenging decisions. Such decisions can affect their psychological wellbeing. Participating in or observing an event or situation that conflicts with personal values can potentially lead to the development of moral injury. Common stressors associated with moral injury include betrayal, inability to prevent death or harm, and ethical dilemmas. Potentially psychologically traumatic event exposures and post-traumatic stress disorder can be comorbid with moral injury; however, moral injury extends beyond fear to include spiritual, cognitive, emotional or existential struggles, which can produce feelings of severe shame, guilt, and anger. Objective This scoping review was designed to identify the extant empirical research regarding the construct of moral injury, its associated constructs, and how it relates to moral distress in firefighters, paramedics, and police officers. Methods A systematic literature search of peer-reviewed research was conducted using databases MEDLINE, EMBASE, APA PsychInfo, CINHAL PLUS, Web of Science, SCOPUS, and Google Scholar. Included studies were selected based on the inclusion criteria before being manually extracted and independently screened by two reviewers. Results The initial database search returned 777 articles, 506 of which remained after removal of duplicates. Following review of titles, abstracts, and full texts, 32 studies were included in the current review. Participants in the articles were primarily police officers, with fewer articles focusing on paramedics and firefighters. There were two studies that included mixed populations (i.e., one study with police officers, firefighters, and other emergency service workers; one study with paramedic and firefighter incident commanders). Most studies were qualitative and focused on four topics: values, ethical decision-making, organizational betrayal, and spirituality. Conclusion Public safety organizations appear to recognize the experience of moral distress or moral injury among public safety personnel that results from disconnects between personal core values, formal and informal organizational values, vocational duties, and expectations. Further research is needed to better understand moral distress or moral injury specific to public safety personnel and inform training and treatment in support of public safety personnel mental health.